The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4049/jimmunol.174.10.6005
|View full text |Cite
|
Sign up to set email alerts
|

IFN Regulatory Factor-2 Deficiency Revealed a Novel Checkpoint Critical for the Generation of Peripheral NK Cells

Abstract: NK cell development is far less understood compared with that of T and B cells despite the critical importance of NK cells in innate immunity. Mice lacking the transcription factor IFN regulatory factor-2 (IRF-2) are known to exhibit NK cell deficiency. However, the role of IRF-2 in NK cell development has remained unclear. In this study we found that NK cell deficiency in the periphery in IRF-2-deficient mice was due to selective loss of mature NK cells, but not to maturation arrest, and NK cells in these mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
77
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 40 publications
(57 reference statements)
4
77
0
Order By: Relevance
“…In this study, we show that the lack of IRF-2 renders macrophages significantly more sensitive to apoptotic stimuli, supporting our previous observations that Kupffer cells from IRF-2 Ϫ/Ϫ mice are more sensitive to apoptosis basally and after LPS (34). Supporting the antiapoptotic function of IRF-2 presented in this work, Taki et al (35) recently reported that bone marrow-derived NK cells from IRF-2 Ϫ/Ϫ mice proliferated almost normally, but underwent accelerated apoptosis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we show that the lack of IRF-2 renders macrophages significantly more sensitive to apoptotic stimuli, supporting our previous observations that Kupffer cells from IRF-2 Ϫ/Ϫ mice are more sensitive to apoptosis basally and after LPS (34). Supporting the antiapoptotic function of IRF-2 presented in this work, Taki et al (35) recently reported that bone marrow-derived NK cells from IRF-2 Ϫ/Ϫ mice proliferated almost normally, but underwent accelerated apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Although IRF-2 has previously been related to apoptosis regulation (34,35,58), the mechanism still remains unclear. In this study, we show that the lack of IRF-2 renders macrophages significantly more sensitive to apoptotic stimuli, supporting our previous observations that Kupffer cells from IRF-2 Ϫ/Ϫ mice are more sensitive to apoptosis basally and after LPS (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by the findings that only CD11b low CD43 À NK cells are present in mice deficient for several different transcription factors, such as GATA-3, IRF2 or T-bet, and in mice bearing constitutively active NFkB. In all these models, the CD11b low CD43 À NK cells exhibit normal cytotoxic capacities [38][39][40][41].…”
Section: Discussionmentioning
confidence: 74%
“…This hypothesis is supported by the findings that only CD11b low CD43 À NK cells are present in mice deficient for several different transcription factors, such as GATA-3, IRF2 or T-bet, and in mice bearing constitutively active NFkB. In all these models, the CD11b low CD43 À NK cells exhibit normal cytotoxic capacities [38][39][40][41].In our study, we found that splenic NK cells from CD70-Tg mice, whether stimulated through the IL-12/IL-18 receptor or through the NK1.1 receptor, produced less IFN-g compared with WT NK cells, whereas in liver no differences were demonstrated. Regarding cytotoxicity, both liver and splenic NK cells from CD70-Tg mice showed increased activity.…”
mentioning
confidence: 75%